2015
DOI: 10.1111/pce.12521
|View full text |Cite
|
Sign up to set email alerts
|

Silicon‐mediated changes in polyamines participate in silicon‐induced salt tolerance in Sorghum bicolorL.

Abstract: Silicon (Si) is generally considered a beneficial element for the growth of higher plants, especially under stress conditions, but the mechanisms remain unclear. Here, we tested the hypothesis that Si improves salt tolerance through mediating important metabolism processes rather than acting as a mere mechanical barrier. Seedlings of sorghum (Sorghum bicolor L.) growing in hydroponic culture were treated with NaCl (100 mm) combined with or without Si (0.83 mm). The result showed that supplemental Si enhanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(107 citation statements)
references
References 65 publications
6
100
0
1
Order By: Relevance
“…For example, Si supplementation has been claimed to influence many physiological parameters based on correlations with elevated polyamine levels (e.g. spermidine, spermine and putrescine) and reduced ethylene signaling in salt‐stressed sorghum (Yin et al ., ), but such observations are far from conclusive in terms of mechanistic evidence. Likewise, claims that Si alleviates K + deficiency‐induced leaf chlorosis by decreasing the accumulation of putrescine are unsubstantiated (Chen et al ., ).…”
Section: Silicon and Abiotic Stress: A Proliferation Of Proposed Mechmentioning
confidence: 99%
“…For example, Si supplementation has been claimed to influence many physiological parameters based on correlations with elevated polyamine levels (e.g. spermidine, spermine and putrescine) and reduced ethylene signaling in salt‐stressed sorghum (Yin et al ., ), but such observations are far from conclusive in terms of mechanistic evidence. Likewise, claims that Si alleviates K + deficiency‐induced leaf chlorosis by decreasing the accumulation of putrescine are unsubstantiated (Chen et al ., ).…”
Section: Silicon and Abiotic Stress: A Proliferation Of Proposed Mechmentioning
confidence: 99%
“…A recent study by Li et al (2016) demonstrated that application of 0.15 mM Spd alleviated the damage caused by salt stress in zoysia ( Zoysia japonica Steud.). Exogenous Spd application also enhanced the salt tolerance of sorghum ( Sorghum bicolor ) seedlings (Yin et al, 2016). Hu et al (2012) also found that exogenous application of 0.15 mM Spm reduced salt injury under salt stress in tomato.…”
Section: Introductionmentioning
confidence: 99%
“…A complementary protective mechanism of plants growing under saline conditions is the synthesis and accumulation of different osmolytes and compatible solutes. Although this is dependent on the plant species, Si has been found to enhance the contents of proline (Tuna et al, 2008; Soylemezoglu et al, 2009; Siddiqui et al, 2014), soluble protein (Li et al, 2015), polyamines (Wang S. et al, 2015; Yin et al, 2016), glycine betaine, total free amino acids, soluble sugars, and phenolic compounds (Abbas et al, 2015). …”
Section: Si Nutrition and Salinity Stressmentioning
confidence: 99%